2021
DOI: 10.3390/plants10040702
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Quantification of Four Marker Compounds in Bauhinia coccinea Extract and Their Potential Inhibitory Effects on Alzheimer’s Disease Biomarkers

Abstract: Bauhinia coccinea is a tropical woody plant widely distributed in Vietnam and Unnan in southern China. Although many studies have shown the biological activities of extracts from various other species in the genus, no studies have investigated the effects of B. coccinea extracts on biological systems. In the present study, a quantitative analysis of four marker compounds of ethanol extracts of B. coccinea branches (EEBC) was performed using the high performance liquid chromatography (HPLC)-photodiode array (PD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…One such in vivo study showed that juice from the leaves of Morus alba had significant protective effects against arsenic-induced neurotoxicity by reducing AChE and BChE level and improved hepatic functioning by restoring normal levels of GSH, SOD, alanine transferase (ALT), aspartate transferase (AST), and alkaline phosphatase (ALP) in Swiss albino mice [ 27 ]. The high-performance liquid chromatography (HPLC)–photodiode array (PDA) method revealed the presence of gallic acid, catechin, ellagic acid, and quercitrin in Bauhinia coccinea , and its ethanolic extract demonstrated neuroprotection through antioxidant activities, as evidenced by the significant inhibition of amyloid-β (Aβ) aggregation and AChE and suppression of hydrogen peroxide (H 2 O 2 )-induced cell death in HT22 neuronal cells in AD [ 28 ]. Among many extracts tested for anti-AD activities, chloroform extract from Enhydra fluctuans was reported to possess the best inhibitory activities, with IC50 values of 83.90 μg/mL and 48.14 μg/mL against AChE and BchE, respectively, and free-radical-scavenging activity was also observed at an IC50 value of 113.27 μg/mL by DPPH radical-scavenging assay, owing to the presence of 19.16 mg gallic acid equivalent/g extract of phenolics and 41.84 mg catechin equivalent/g extract of flavonoids in the extract [ 29 ].…”
Section: Plants and Their Bioactive Compounds In Averting The Pathoge...mentioning
confidence: 99%
“…One such in vivo study showed that juice from the leaves of Morus alba had significant protective effects against arsenic-induced neurotoxicity by reducing AChE and BChE level and improved hepatic functioning by restoring normal levels of GSH, SOD, alanine transferase (ALT), aspartate transferase (AST), and alkaline phosphatase (ALP) in Swiss albino mice [ 27 ]. The high-performance liquid chromatography (HPLC)–photodiode array (PDA) method revealed the presence of gallic acid, catechin, ellagic acid, and quercitrin in Bauhinia coccinea , and its ethanolic extract demonstrated neuroprotection through antioxidant activities, as evidenced by the significant inhibition of amyloid-β (Aβ) aggregation and AChE and suppression of hydrogen peroxide (H 2 O 2 )-induced cell death in HT22 neuronal cells in AD [ 28 ]. Among many extracts tested for anti-AD activities, chloroform extract from Enhydra fluctuans was reported to possess the best inhibitory activities, with IC50 values of 83.90 μg/mL and 48.14 μg/mL against AChE and BchE, respectively, and free-radical-scavenging activity was also observed at an IC50 value of 113.27 μg/mL by DPPH radical-scavenging assay, owing to the presence of 19.16 mg gallic acid equivalent/g extract of phenolics and 41.84 mg catechin equivalent/g extract of flavonoids in the extract [ 29 ].…”
Section: Plants and Their Bioactive Compounds In Averting The Pathoge...mentioning
confidence: 99%